2012
DOI: 10.1007/s11357-012-9423-9
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity to muscle ratio predicts incident physical limitation in a cohort of 3,153 older adults—an alternative measurement of sarcopenia and sarcopenic obesity

Abstract: Conventionally, sarcopenia is defined by muscle mass and physical performance. We hypothesized that the disability caused by sarcopenia and sarcopenic obesity was related to the amount of adiposity or body weight bearing on a unit of muscle mass, or the adiposity to muscle ratio. We therefore examined whether this ratio could predict physical limitation by secondary analysis of the data in our previous study. We recruited 3,153 communitydwelling adults aged >65 years and their body composition was measured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 39 publications
1
52
0
Order By: Relevance
“…In other words, the LBM/FM ratio rather than the absolute FM and LBM of a person is the most relevant parameter to consider when the mechanical or physiological consequences of PAs are investigated. Several studies have indicated that the beneficial effects of PA are most likely mediated through an increase in LBM relative to FM (Auyeung, Lee, Leung, Kwok, & Woo, 2013;Haight et al, 2005;Tager, Haight, Sternfeld, Yu, & van Der Laan, 2004). These results provide further support for the hypothesis that regular qigong practice can increase the LBM/FM ratio.…”
Section: Discussionsupporting
confidence: 71%
“…In other words, the LBM/FM ratio rather than the absolute FM and LBM of a person is the most relevant parameter to consider when the mechanical or physiological consequences of PAs are investigated. Several studies have indicated that the beneficial effects of PA are most likely mediated through an increase in LBM relative to FM (Auyeung, Lee, Leung, Kwok, & Woo, 2013;Haight et al, 2005;Tager, Haight, Sternfeld, Yu, & van Der Laan, 2004). These results provide further support for the hypothesis that regular qigong practice can increase the LBM/FM ratio.…”
Section: Discussionsupporting
confidence: 71%
“…In addition, older adults usually have become shorter, which could lead to an overestimation of muscle mass with the formula ALM/height squared. Therefore, it is important to take muscle mass relative to body mass or fat mass into account when defining sarcopenia (Delmonico et al 2007;Newman et al 2003;Auyeung et al 2012). In this study, muscle strength, in particular knee extension torque, was associated with the TUG test and walking speed in old participants, but not with physical fitness.…”
Section: Discussionmentioning
confidence: 76%
“…present study, we used F/L mass ratios and found them to be associated with nutritional and inflammatory status, and to be acceptable new predictors of long-term outcomes in patients undergoing HD. The fat-to-muscle ratio was recently proposed to differentiate among obesity phenotypes, and this ratio has been associated with physical performance in elderly individuals [24,25]. This ratio has also been associated with metabolic dysfunction in women with polycystic ovarian syndrome [21].…”
Section: Discussionmentioning
confidence: 99%